Vertical distribution of harmful algae in the sediment of Uranouchi Inlet by metabarcoding - Funaki, Hiroshi; Gaonkar, Chetan Chandrakant; Nishimura, Tomohiro; Tanaka, Kouki; Kamimura, Kaito; Kaji, Tatsuya; Nagasaki, Keizo; Adachi, Masao (Frontiers in Protistology, 2025)
Uranouchi Inlet, situated on the Pacific coast of southwestern Japan, has been a highly enclosed inlet known for yellowtail farming since 1959. Since the 1980s, harmful algal blooms (HABs) have repeatedly occurred, resulting in mass mortality of fish and shellfish. In the sediment at the inlet, the resulting cysts of the HAB species may be preserved, which reflects the history of HAB events. However, the vertical distributions of HAB species in sediment have not been elucidated. In this study, core sediment samples were analyzed by metabarcoding. The dating of each sample was cited from previous study dating the same samples. The findings revealed the presence of eleven HAB species, with notable shifts from approximately 1977–1988. The timing of the shifts corresponded to that of the development of aquaculture and the resulting eutrophication. Vertical core metabarcoding provides footprints of how HAB species composition may be influenced by anthropogenic environmental changes.